RE: Comment On: Association of HOTAIR rs1899663 G>T Polymorphism with Colorectal Cancer in the Turkish Population: A Case–Control Study - Berrin Yalınbaş Kaya,; Betül Peker,; Fuzuli Tuğrul,; Özge Alkan Tali,; Süleyman Bayram, (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Yalınbaş Kaya B, Peker B, Tuğrul F, Alkan Tali Ö, Bayram S. RE: Comment on: Association of HOTAIR rs1899663 G>T polymorphism with colorectal cancer in the turkish population: A case–control study. Turk J Gastroenterol. 2023;34(7):780.